Incidence and Survival of Patients with Small Intestinal Neuroendocrine Tumours in a Danish NET Center - Lise Brehm Hoej; Karen Marie Nykjær; Henning Gronbaek (The Scientific World Journal)
Introduction. Small intestinal neuroendocrine tumours (NETs) have increased in incidence during the past decades. In recent years, new promising treatment modalities have been introduced. The aim of the present study was to characterize and compare patients with small intestinal NET seen in the periods 1994–2003 (group 1) and 2004–2011 (group 2) to demonstrate changes in incidence and survival in the two time periods. Patients and Methods. There were 52 NET patients in group 1 and 109 patients in group 2. Results. The incidence of small intestinal NET was 0.3/100.000/year in period 1 and 0.7/100.000/year in period 2. There was no difference in median chromogranin A levels (8709 versus 2381 pmol/L, P=0.107), presence of liver metastases (56% versus 44%), clinical symptoms (flushing/diarrhea), or Ki67 index (2% versus 2%), between the two time periods. The 5-year survival rate in the two time periods was similar, 64.7%, and 77.0%, respectively, (P=0.23). Conclusion. We observed an increase in the incidence of small intestinal NET during the period from January 1994 to December 2011, but we were not able to demonstrate an improved survival during the same time period.